Comparative Legal Analysis of the Obligations of Kazakhstan and the CIS Countries on Nuclear Disarmament - Bolat, Alibek; Saimova, Sholpan (Brawijaya Law Journal, 2025)
This study conducts a comparative analysis of Kazakhstan’s and CIS countries’ nuclear disarmament commitments. The primary aim of the research is to identify convergences and divergences in legal obligations, policy frameworks, and implementation mechanisms across the region. The work holds both scientific values, by filling a gap in comparative regional nuclear policy studies, and practical relevance, by informing policymakers on best practices. Employing a comparative legal methodology, supplemented by document analysis and expert interviews, the research examines treaties, domestic legislation, and compliance reports. Key findings reveal that Kazakhstan demonstrates leadership through proactive treaty accession and verification measures, while some CIS states face implementation delays due to political and technical constraints. The study contributes to international security scholarship by clarifying regional disarmament dynamics and offers recommendations to enhance cooperative mechanisms and strengthen national institutions for effective disarmament. Practical significance lies in guiding future policy harmonization and capacity-building initiatives.